Caracterización de suelo del Sector Prusia, Parque Nacional Volcán Irazú, con mira en la rehabilitación ecológica. - Padilla-Rojas, Ania (Instituto Tecnológico de Costa Rica, 2017)
The Prusia Sector has a reforestation of about 52 years, which begins to show signs that it has reached the self-thinning, without being clear, for the moment, about the most appropriate management techniques and the effects that these techniques could have on soil. In order to characterize the physical-chemical properties in Prussia, physical and chemical soils were sampled under three coverings (Cypress, Pine, and Eucalyptus). The physical characteristics analyzed presented similar results among the different species, so no evidence was found that the species could have affected the soil in a differentiated way. With the result of this investigation, it will be possible to demonstrate the effects that a restoration process may have in the future in the sector, thus allowing to choose the best technique.
Proyecto de Graduación (Licenciatura en Ingeniería Forestal) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2017.
Keywords: Propiedades químicas; Propiedades físicas; Reforestación; Suelo; Forestal